N1, N1, N3, N3-tetra([1, 1′-biphenyl]-4-yl)-N5, N5-diphenylbenzene-1, 3, 5-triamine: Synthesis, optical properties and application in OLED devices as efficient hole transporting material. (November 2015) - Yin, Zhiguo; Liu, Rui; Li, Chong; Masayuki, Tanigawa; Liu, Caozhi; Jin, Xiaodong; Zhu, Hongjun
Abstract: A hole-transporting material, N 1, N 1, N 3, N 3 -tetra([1, 1′-biphenyl]-4-yl)- N 5, N 5 -diphenylbenzene-1, 3, 5-triamine (TDAB-BP ), was synthesized by di([1, 1′-biphenyl]-4-yl)amine and 3, 5-dichloro- N, N -diphenylaniline via Buchwald–Hartwig coupling reaction. The material exhibit high hole mobility, excellent thermal and morphological stability. TDAB-based OLED device exhibited the highest performance in terms of the maximum current efficiency (9.34 cd/A), maximum power efficiency (5.89 lm/W), and maximum external quantum efficiency (6.61%), which is significantly improved than that of the standard device based on 4, 4′-bis[ N -(1-naphthyl)- N -phenyl-amino]-biphenyl (NPB) (7.12 cd/A, 4.90 lm/W and 5.31%). Furthermore, TDAB-BP shows a higher decomposition temperature ( T d ) of 505 °C than that of NPB (418 °C). This material could be a promising hole-transporting material, especially for the high-temperature applications of OLEDs and other organic electronic devices. Graphical abstract: A hole-transporting materialTDAB-BP was synthesized, which exhibits high hole mobility, excellent thermal and morphological stability. Blue OLED device based onTDAB-BP exhibits high performance with the maximum current efficiency of 9.34 cd/A, maximum power efficiency of 5.89 lm/W and maximum external quantum efficiency of 6.61%.TDAB-BP could significantly improve the device performance than traditional NPB. Highlights: A hole transporting material was synthesized and characterized. The compound exhibits high hole mobility and excellent thermal stability. The resulting device exhibits higher efficiency compared with NPB-device.